2014
DOI: 10.1002/mnfr.201300818
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide treatment ameliorates the course of experimental colitis mediated by enhanced neutrophil‐specific antibacterial clearance

Abstract: Pharmacological application of NAM mediates beneficial effects in bacterial and chemically induced colitis. Future studies are needed to explore the clinical potential of NAM in the context of intestinal bacterial infections and human inflammatory bowel disease (IBD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 52 publications
(75 reference statements)
1
30
0
1
Order By: Relevance
“…IBD is bound to be closely related to the metabolic disorder of bile acids, especially to reduce the level of secondary bile acids, while hydrophilic secondary bile acids have cytoprotective effects. In this study, the down-regulation of taurodeoxycholic acid, chenodeoxycholic acid and bile acid in plasma of colitis rats was verified this point ( Blackwood et al, 2011 ; Disher et al, 2014 ).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…IBD is bound to be closely related to the metabolic disorder of bile acids, especially to reduce the level of secondary bile acids, while hydrophilic secondary bile acids have cytoprotective effects. In this study, the down-regulation of taurodeoxycholic acid, chenodeoxycholic acid and bile acid in plasma of colitis rats was verified this point ( Blackwood et al, 2011 ; Disher et al, 2014 ).…”
Section: Discussionsupporting
confidence: 68%
“…Compared with the normal group, the levels of niacinamide in TNBS-induced colitis was decreased. Studies have shown that nicotinamide enhanced the antimicrobial activity of neutrophil, improved tissue damage and reduced the activity of MPO of DSS-induced colitis mice significantly ( Disher et al, 2014 ; Dominik et al, 2014 ). Consistent with previous studies, the levels of linoleic acid and arachidonic acid were decreased and the leukotriene A4 was increased in colitis rats.…”
Section: Discussionmentioning
confidence: 99%
“…In human gastroenterology, the evaluation of serum AAs is a non-invasive, predictive marker of intestinal inflammation, and the supplementation of AAs can attenuate this inflammation and improve clinical signs and weight gain [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…5,9,10 There is an anti-inflammatory effect of dietary intervention with tryptophan or tryptophan metabolites in experimental models of colitis, with supplementation ameliorating clinical signs, improving weight gain and histological scores and decreasing gut permeability and expression of proinflammatory cytokines. 11,12 Similarly, supplementation with glutamine, arginine, N-acetylcysteine, and glycine in animal models of IBD has beneficial effects such as reduced intestinal permeability and decreased production of proinflammatory cytokines. [13][14][15][16] Dogs with protein-losing enteropathy (PLE) have increased loss of protein from the intestinal tract resulting in hypoproteinemia.…”
mentioning
confidence: 99%